2004
DOI: 10.1021/ol0486829
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Stereospecific Synthesis of Glycosyl Cyanides from 1,2-O-Sulfinyl Derivatives

Abstract: [reaction: see text] An efficient synthesis of 1,2-trans-glycosyl cyanides via 1,2-O-sulfinyl monosaccharides is described. Such S(N)2-type displacements at the anomeric center are stereospecific and are best performed with sodium cyanide in the presence of ytterbium triflate. Significantly, the resulting 1,2-trans-glycosyl cyanides have a free hydroxyl group at C-2 ready for further modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…. 20 To a solution of compound 5a (12.9 g, 25.7 mmol) in dry diethyl ether (16.0 mL) was added a saturated solution of ammonia in MeOH (193 mL) at rt. The reaction mixture was stirred for 24 h (until TLC indicated complete conversion).…”
Section: 46-tri-o-benzyl-β-d-galactopyranosyl Cyanide (6a)mentioning
confidence: 99%
“…. 20 To a solution of compound 5a (12.9 g, 25.7 mmol) in dry diethyl ether (16.0 mL) was added a saturated solution of ammonia in MeOH (193 mL) at rt. The reaction mixture was stirred for 24 h (until TLC indicated complete conversion).…”
Section: 46-tri-o-benzyl-β-d-galactopyranosyl Cyanide (6a)mentioning
confidence: 99%
“…15 However Beaupere reported that such cyclic sulfites could be obtained for the pyranose form of arabinose. 8 In order to establish whether direct access to cyclic sulfites and sulfates species could be formed from 1,2-and 3,5-deprotected sugars (Scheme 1), the reactions of a series of sugar-diols (Table 1, 1-4) and bases with thionyl chloride were investigated.…”
Section: Synthesis Of Cyclic Sulfites and Sulfates In Ils And Moleculmentioning
confidence: 99%
“…Similarly, cyclic sulfite/sulfate esters have had limited applications due to problems associated with their syntheses 4,6,7 (e.g., difficulties in controlling cyclisation vs chlorination), as well as their variable reactivity towards nucleophiles. 8,9 For example, there are currently only two reported procedures used to prepare 1,2-cyclic sulfites from 1,2-diols. These involve thionyl chloride or N,N 0 -thionyl diimidazole in pyridine under anhydrous and temperature controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syntheses of 1-C-aminomethyl glycosides so far described rely on the introduction of a CH 2 NH 2 equivalent at the anomeric position: (a) as CH 3 NO 2 via nucleophilic aldol reaction, 7 (b) by reducing the corresponding glyco-syl cyanide 8 or, (c) by degradation of a C-vinyl glycoside and subsequent formation of the azidomethyl intermediate. 3b Alternatively, rearrangement involving 5-exo S N 2opening of a terminal aziridine ring, and transformation of a primary hydroxyl function into the corresponding azide gave access to the 2,5-anhydro derivatives 3 4 and 4, 9 respectively.…”
mentioning
confidence: 99%